Ефективність використання газового змащення при проколюванні ґрунту - Руднєв, В. К.; Супонєв, В. М.; Хачатурян, С. Л. (НТУ "ХПІ", 2013)
У статті визначено зусилля опору ґрунту проколюванню конічним робочим органом і на його основі встановлено значення показника ефективності зниження вказаного зусилля за рахунок використання ефекту газового змащення в залежності від кута загострення робочого органу та коефіцієнта зовнішнього тертя ґрунту.

The results of the complex diagnosis of the water-heating aggregate based on the pyrolized heat-generator with output of 900 kW working on the fuel from wood waste. It is determined that technological and ecological features of the aggregate correspond up-to-date requirements and the usage of this aggregate in the communal branch helps to reduce significantly tariffs to hot and cold water supply
Results of tests of industrial implementation of pyrolized heat-generators
Keywords: газоповітряне змащення; грунтооброблюючі машини; ґрунт; коефіцієнт зовнішнього тертя